Vitamin-D Deficiency As a Potential Environmental Risk Factor in Multiple Sclerosis, Schizophrenia, and Autism - Kočovská, Eva; Gaughran, Fiona; Krivoy, Amir; Meier, Ute-Christiane (Frontiers in Psychiatry, 2017)
In this short review, we want to summarize the current findings on the role of vitamin-D in multiple sclerosis (MS), schizophrenia, and autism. Many studies have highlighted hypovitaminosis-D as a potential environmental risk factor for a variety of conditions such as MS, asthma, cardiovascular disease, and, more recently, psychiatric diseases. However, whether hypovitaminosis-D is a potential causative factor for the development or activity in these conditions or whether hypovitaminosis-D may be due to increased vitamin-D consumption by an activated immune system (reverse causation) is the focus of intense research. Here, we will discuss current evidence exploring the role of vitamin-D in MS, schizophrenia, and autism and its impact on adaptive and innate immunity, antimicrobial defense, the microbiome, neuroinflammation, behavior, and neurogenesis. More work is needed to gain insight into its role in the underlying pathophysiology of these conditions as it may offer attractive means of intervention and prevention.